Application of DNA barcoding confirms the female, male, larva and host of Bocchus scobiolae Nagy (Hymenoptera: Dryinidae) - Olmi, Massimo; Mita, Toshiharu; Guglielmino, Adalgisa; Vollaro, Massimo; Vári, Gábor (Zootaxa, 2021)
Bocchus scobiolae Nagy (Hymenoptera: Dryinidae, Bocchinae) was reared in Szeged, Hungary. The female, male and immature larva were associated by mitochondrial COI sequences. B. scobiolae, previously known only from Romania, is recorded for the first time from Hungary, Moldova, and Turkey. Caliscelis wallengreni (Stål) (Hemiptera: Caliscelidae) is mentioned for the first time as host of B. scobiolae. B. vernieri Olmi is indicated for the first time from Hungary. Helegonatopus rasnitzyni (Trjapitzin, 1963) (Hymenoptera: Encyrtidae), recorded for the first time from Hungary, was reared from B. scobiolae (new record).